2016
DOI: 10.1097/md.0000000000005144
|View full text |Cite
|
Sign up to set email alerts
|

The research on long-term clinical effects and patients’ satisfaction of gabapentin combined with oxycontin in treatment of severe cancer pain

Abstract: Gabapentin has been used as an adjuvant for treatment of cancer pain. Previous studies showed that opioids combined with gabapentin for management of cancer pain reduced the dosage of opioids.The objective of this study was to explore the clinical effect and patients’ satisfaction of oxycontin combined with gabapentin in treatment of severe cancer pain. After titration of morphine, 60 severe cancer patients with visual analog score (VAS) more than 7 were randomly divided into trial group (n = 30) and control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…39 They have been studied primarily in noncancer neuropathy syndromes, 40 although data exist supporting their use for treatment of cancer pain in conjunction with opioids. 41,42 Gabapentin has been reported to reduce mucositis pain in patients receiving concomitant radiotherapy and chemotherapy. 43 When compared in a prospective, randomized, open-label trial, pregabalin relieved neuropathic cancer-related pain more effectively than transdermal fentanyl.…”
Section: Adjuvant Analgesicsmentioning
confidence: 99%
“…39 They have been studied primarily in noncancer neuropathy syndromes, 40 although data exist supporting their use for treatment of cancer pain in conjunction with opioids. 41,42 Gabapentin has been reported to reduce mucositis pain in patients receiving concomitant radiotherapy and chemotherapy. 43 When compared in a prospective, randomized, open-label trial, pregabalin relieved neuropathic cancer-related pain more effectively than transdermal fentanyl.…”
Section: Adjuvant Analgesicsmentioning
confidence: 99%
“…After 179 relevant articles were assessed for eligibility through a full-text evaluation, 43 studies with 6,537,444 patients were selected. TRAEs were reported in 26 RCTs ( Caraceni et al, 2004 ; Gilron et al, 2005 ; Fassoulaki et al, 2006 ; Turan et al, 2006 ; Keskinbora et al, 2007 ; Clarke et al, 2009 ; Gatti et al, 2009 ; Clendenen et al, 2010 ; Rapchuk et al, 2010 ; Pesonen et al, 2011 ; Yucel et al, 2011 ; Chaparro et al, 2012 ; Jain et al, 2012 ; Pota et al, 2012 ; Yadeau et al, 2012 ; Mercadante et al, 2013 ; Paul et al, 2013 ; Clarke et al, 2015 ; Chen et al, 2016 ; Dou et al, 2017 ; Wang et al, 2017 ; Hah et al, 2018 ; Jones et al, 2019 ; Hermann et al, 2020 ; Jung et al, 2020 ; Teng et al, 2021 ) and 7 non-RCTs ( Caraceni et al, 1999 ; Li et al, 2010 ; Savelloni et al, 2017 ; Peckham et al, 2018 ; Bykov et al, 2020 ; Chae et al, 2021 ; Dai et al, 2021 ); mortality was reported in 10 non-RCTs. ( Abrahamsson et al, 2017 ; Gomes et al, 2017 ; Gomes et al, 2018 ; Slavova et al, 2018 ; Macleod et al, 2019 ; Lynn et al, 2020 ; Waddy et al, 2020 ; Bishop-Freeman et al, 2021 ; Mariottini et al, 2021 ; Chen et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…This meta-analysis included only randomized controlled trial (RCT) studies that mostly focused on the short-term use of perioperative analgesics. However, gabapentinoids are prescribed for long-term use for cancer-associated or non-cancer chronic pain, and their medication use could be different from RCT studies in actual clinical settings ( Chen et al, 2016 ; Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No previous studies had demonstrated any findings that gabapentin might play a role in inflammation and in immunomodulation in an in vivo tumor model. These findings are relevant because gabapentin is frequently used in the management of severe pain, especially in cancer patients [16, 17].…”
Section: Discussionmentioning
confidence: 99%